Dinamika rasio net profit margin (npm) bank mega syariah selama 2020–2024 - Azis, Abd (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the dynamics of Bank Mega Syariah’s Net Profit Margin (NPM) during the 2020–2024 period as a key indicator of the bank’s profitability and operational efficiency. NPM is calculated based on annual net profit and operating income data to assess the bank’s ability to generate profits amidst changing economic conditions, from the pressures of the COVID-19 pandemic to the recovery and digitalization phase of banking. The analysis results show that Bank Mega Syariah’s NPM fluctuated significantly, with the lowest value in 2020 at 16.09% due to the impact of the global economic crisis, jumping to 46.0% in 2021 due to the impact of economic recovery and cost efficiency, and stabilizing at around 27–29% during 2022–2024, reflecting the bank’s ability to maintain profitability through strengthening service digitalization and more effective operational management. These findings indicate that NPM provides an important overview of the bank’s financial performance, as well as being a relevant indicator for management, investors, and regulators in assessing the health and resilience of Bank Mega Syariah.